Implementação e avaliação de modelos de mobilidade de dispositivos no simulador MyiFogSim - Marques, Bruno Schmidt (2019)
Fog Computing proposes an architecture capable of flexibilizing and optimizing distributed applications, hosting them closer to its consumers. However, the difficulty of accessing real Fog Computing environments causes researchers to use simulators to develop new contributions in this area. One of the main shortcomings found in the current ’Fog Computing’ simulators is the simplification of the device mobility model. This work presents the implementation of mobility models for mobile devices in Fog Computing environments through the extension of the MyiFogSim simulator. In addition, the impact of different mobility models on the scalability and latency of applications, as well as the MyiFogSim virtual machine scheduler, is analyzed.